2021
DOI: 10.1002/aqc.3653
|View full text |Cite
|
Sign up to set email alerts
|

Improving breed‐and‐release programmes in the face of a threatening pathogen, Batrachochytrium dendrobatidis

Abstract: As the proportion of threatened species increases, so too does the need for effective conservation strategies. In response, captive breed‐and‐release and habitat mitigation programmes are two conservation actions that are increasing in use and effectiveness. Success of these programmes is frequently hampered by the continued presence of threatening processes. In the case of amphibian reintroductions, a key threatening process that is difficult to eliminate is the deadly fungal pathogen, Batrachochytrium dendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…It may be possible to create a future where species impacted by unnatural wildfires due to anthropogenic climate change can be protected (Shoo et al, 2011). We encourage research exploring options to bolster climate change adaptations within the paradigms of genetic management (Cummins et al, 2019), cryopreservation (Clulow & Clulow, 2016), reintroduction (Klop‐Toker et al, 2021) and habitat restoration (Beranek et al, 2021). However, these efforts may only offer a temporary solution because without global action to reverse or halt further climate change, wildfires are predicted to become larger and more severe, reducing the distributions of many forest‐dependent amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to create a future where species impacted by unnatural wildfires due to anthropogenic climate change can be protected (Shoo et al, 2011). We encourage research exploring options to bolster climate change adaptations within the paradigms of genetic management (Cummins et al, 2019), cryopreservation (Clulow & Clulow, 2016), reintroduction (Klop‐Toker et al, 2021) and habitat restoration (Beranek et al, 2021). However, these efforts may only offer a temporary solution because without global action to reverse or halt further climate change, wildfires are predicted to become larger and more severe, reducing the distributions of many forest‐dependent amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overwhelming evidence of the negative impacts of chytrid, our literature review revealed that there have been few attempts to implement conservation actions across wild populations, with only a handful of studies attempting in situ actions to reduce the impacts of this disease. Three studies have manipulated different pond and water dynamics to reduce the infection load of chytrid [145,181,182]. As chytrid infection rates are positively correlated with cooler temperatures and a more neutral pH (optimal 6-7.5), Klop-Toker et al [181] manipulated temperature and salinity levels within discrete breeding ponds to establish persistent breeding populations of the endangered green and gold bell frog Litoria aurea.…”
Section: Mitigating Chytrid Within the Terrestrial Environmentmentioning
confidence: 99%
“…Three studies have manipulated different pond and water dynamics to reduce the infection load of chytrid [145,181,182]. As chytrid infection rates are positively correlated with cooler temperatures and a more neutral pH (optimal 6-7.5), Klop-Toker et al [181] manipulated temperature and salinity levels within discrete breeding ponds to establish persistent breeding populations of the endangered green and gold bell frog Litoria aurea. However, the study produced mixed results, with frog populations in manipulated ponds still reporting high chytrid loads across the four years.…”
Section: Mitigating Chytrid Within the Terrestrial Environmentmentioning
confidence: 99%
See 1 more Smart Citation